Membangun Papua dengan Formulasi Tradisi Lisan - Jonner Sianipar (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Each tribe at Papua is ensured have oral tradition by itself. The oral tradition misses fire by itself. Even, oral tradition comes into the world as expression of society dynamics with moral values, norm, manner, and local character. Those values as society identity, as well in internal community and also external. Papuan oral tradition will more effective if it shaped in a grand design or scheme on grows arranged by comprehensive and permanent for development formulation at Papua Province.